Neutrophil to lymphocyte ratio is increased in chronic helicobacter pylori infection and returns to normal after successful eradication (Annals of Medical Research, 2021)
Aim: Neutrophil to lymphocyte ratio (NLR) is a useful, low cost marker and it was studied in several diseases. This study was conducted to investigate NLR in chronic Helicobacter pylori infection.
Keywords: Neutrophil To Lymphocyte Ratio; Helicobacter Pylori, disease eradication